2018
DOI: 10.1007/s13193-018-0770-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Gastrointestinal Cancers in a Single Patient—a Rare Clinical Entity

Abstract: Multiple gastrointestinal cancers in a single patient is a rare entity. In our study, we are showing the clinical presentation and management of these patients. A fifty-nine-year-old asthenic male (already treated case of metachronous colorectal cancer in 2008 and 2011) presented with complaints of generalized weakness and fatigue. Strong family history was present with two of his first-degree relatives having diagnosed with gastrointestinal cancer at the age < 50 years with one of them having stomach carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Sahni et al reported a metachronous gastric cancer 10 years after colorectal cancer in a patient with a significant family history of gastrointestinal malignancies and unidentifiable gene mutation. The patient was managed with radical total gastrectomy and adjuvant chemotherapy [ 18 ]. Our patient presented with metastatic metachronous gastric cancer 4 years after surgical resection of rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Sahni et al reported a metachronous gastric cancer 10 years after colorectal cancer in a patient with a significant family history of gastrointestinal malignancies and unidentifiable gene mutation. The patient was managed with radical total gastrectomy and adjuvant chemotherapy [ 18 ]. Our patient presented with metastatic metachronous gastric cancer 4 years after surgical resection of rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammatory bowel diseases (IBD) or family history of CRC are the primary causes of CRC [4]. In economically developed countries, the mortality connected to CRC is greater than the economically developing nations, and it affects over a million people annually [5]. Several epidemiological studies have also shown different risk factors to CRC including age, family history, IBD, obesity, smoking, lack of exercise, alcohol consumption, and diet [6].…”
Section: Introductionmentioning
confidence: 99%